Challenges Of The Recognition Of Competences Acquired Informally And Non-Formally By Vocational Education And Training Teachers: Reflections Based On The EU’s Experience - Planas, Jordi (Journal of Technical Education and Training, 2009)
Vocational Education and Training (VET) Teachers have usually had a characterized by complex and diversified learning process. A large number of VET teachers have mixed professional pathways – both teaching and working outside the educational system. This mixed experience is considered in the VET centres as a guarantee of better teaching, because the teachers are more familiar with working life. The socioeconomic networking activities of VET centres highlight the as social networking capacity. For this reason the recognition of competences acquired non-formally or informally by VET teachers takes a central place in the careers of VET teachers. Would it be useful to incorporate this mechanism of recognition in the “trans-national standards of teachers’ education for VET?” For several decades now there has been in the EU context a debate on the mechanisms for recognition of competences acquired non-formally or informally. The speaker intends to discuss the recognition of the competences acquired by VET teachers in non-formal and informal ways based on the experience of recognition of prior learning in the EU.